Pattern of Head Injury and Associated Injuries in the Patients Presenting to Neurosurgical Emergency - Salman Raza, Yasir Shahzad, Shafiq-ur-Rahman, Ali Tassadaq, Nadeem Akhtar, Salman Raza, Yasir Shahzad, Shafiq-ur-Rahman, Ali Tassadaq, Nadeem Akhtar (Journal of Rawalpindi Medical College, 2018)
Background: To assess the pattern of head injury and associated injuries along with head injury presenting to neurosurgical emergency after sustaining injuries by different modes. Methods: In this observational study, non-probability consecutive sampling was used. Patients were recruited who were having head injury with or without any associated bodily injury. There was no compulsion for age and gender Results:Majority of the patients were male (81.28%) with 48% aged between 20-49 years. Road traffic accident (66.89%) was the commonest mode of injury. Associated injuries were found in 39.7%. Maxillo-facial injury ( 17.3%), long bone injury (17.8%) and spinal trauma (5.8%) were the commonest associated injuries.Normal brain CT scan was seen in 28.6% Conclusion: Head injury is frequently associated with injuries to other parts of body .That is why other bodily injuries should be taken into consideration while dealing with head injury.